Ferdinand Ebner - Mühlauer Tagebuch 23.7.-28.8.1920 Edition und Kommentar - Hörmann, Richard (2001)
Ferdinand Ebner is next to Ludwig Wittgenstein the most important Austrian philosopher of language in the 20th century. In his main work Das Wort und die geistigen Realitäten. Pneumatologische Fragmente Ebner produces a new form of anthropology, which is based on a dialogic orientated understanding of human beings. Beside his philosophical works Ebner wrote many letters and diaries. One of the 14 existing diaries is the so-called "Mohlauer Tagebuch" from the 23rd of July to the 28 th of August 1920, which is kept on the "Brenner Archiv" in Innsbruck together with the philosophical texts and the letters. In this diary Ebner writes about his stay in Mühlau, a village near Innsbruck, where he was a guest of Ludwig von Ficker for one month and which was the beginning of a long friendship with the publisher of the Brenner. Ficker, who had already published some articles of Ebner in the Brenner, printed the Fragmente 1921, two years after Ebner wrote them. In this way Ficker became the publisher, promoter and friend of Ebner. According to some passages of the diary, Ebner experienced in Ficker a kind of acceptance and security, which he did not know before. This feeling of well-being is also a part of the deep impressions of nature, which Ebner got on many walks through the surrounding of Innsbruck. Although he was a thinker, who always emphasized the meaning of the word, these impressions showed him the limits of language. Ebner's basic opinions are presentated very clearly in his meetings with different members of the Brenner-circle and in the confrontation with the intellectual movements of the time. An example are his talks with Paul Bargehr about Buddhism, who was newly rediscovered in Europe in those days. Ebner understood the good will of Bargehr, but he cannot accept Buddhism as a solution for the big problems of the Europeans. In spite of Ebners turn to Christianity some years before the diary also shows the difficulties in the relation between Ebner and the Catholic church. Of special interest is Ebner's meeting with the painter Erich Lechleitner. In front of Lechleitner's pictures he has doubts about his radical pessimism concerning art and culture. The text of the diary is followed by a commentary, which explains the biographical, literary, philosophical, historical, etc. connections of passages in the diary. The three essays following the commentary give an overview of Ebners biographical, philosophical and cultural background. Monika Seekircher's essay includes a short biography of Ebner and describes the most important personal relations in his life as well as his intellectual developement. Richard Hörmann tries to show the connections between the diary and the Fragmente, because many entries of the diary can only be understood on the basis of the main thoughts of the Fragmente. The topic of Walter Methlagl's essay is the local cultural context, in which the diary is embedded. Special attention is given to the intellectual movements within the Brenner-circle. The numerous photos depict persons, who are mentioned in the diary, places as they then looked and the pictures by painters named in the diary.